On monotone ill-posed problems in Hilbert spaces - Bường, Nguyễn (Journal of Computer Science and Cybernetics, 2016)
The main aim of this paper is to study convergence rates for an operator method of  regularization to solve nonlinear ill-posed problems involving monotone operators in infinite-dimentional Hilbert space without needing closeness conditions. Then these results are presented in form of  combination with finite-dimentional approximations of the space. An iterative method for solving regularized equation is given and  an example in the theory of singular integral equations is considered for illustration.